COVID-19 scoring - Das, Sayonee; Ray, Abhijit (International Journal of Advances in Medicine, 2020)
Background: Triaging of COVID-19 patients. Coronavirus disease 2019 (COVID-19) pandemic has posed a threat both to lives of common people as well as to the existing overburdened healthcare system. There has been dearth of hospital beds which has lead to chaos. In such a situation triaging of patients is of utmost importance to avoid unnecessary hospital admission which results in both anxiety in patients and increases load on hospitals. We hereby propose a scoring system which incorporates all the points that must be seen in suspected and tested positive COVID-19 patients and gives a score following which patients can be divided into different stages as per severity namely mild, moderate and severe. Mild cases can be advised for home quarantine/isolation with warning signs explained and this reduces unnecessary admissions. Moderate and severe cases which requires admission can be triaged with respect to ward and intensive care unit (ICU) admissions. This prevents unnecessary ICU admissions as well as prevents delay in ICU shifting of moderate cases on deterioration. Methods: We have conducted a cross-sectional study on 500 suspected and real time-polymerase chain reaction (RT-PCR) tested positive COVID-19 patients using this scoring system in order to triage them. Result: Out of 500 patients including both suspected and positive COVID-19 patients only 373 required admissions whereas 127 admissions were successfully avoided as they could be sent for home quarantine/isolation. Conclusion: Triaging of patients, especially during a pandemic where the case load is immense, is very important. Presence of a concise score which incorporate all important points serves the purpose.